Chelovek nedeli . Chelovek nedeli . Person of the Week . Человек недели - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Interview with the director of a joint stock company "Trekhgornaia Manufaktura" Nadezhda Balanovskaia. Series description: Interviews with outstanding personalities - politicians, scientists, cultural figures. Was on air from January 8, 1993 until July 21, 1995. Беседа с директором акционерного общества "Трехгорная мануфактура" Надеждой Балановской. Описание серии: Интервью с выдающимися личностями - политиками, учеными, деятелями культуры. Ток-шоу выходило с 8 января 1993 по 21 июля 1995 года.